Inhibition of attachment of oral bacteria to immortalized human gingival fibroblasts (HGF-1) by tea extracts and tea components - Wang, Y.; Chung, F.; Lee, S.; Dykes, Gary (2013)
Background: Tea has been suggested to promote oral health by inhibiting bacterial attachment to the oral cavity. Most studies have focused on prevention of bacterial attachment to hard surfaces such as enamel. Findings: This study investigated the effect of five commercial tea (green, oolong, black, pu-erh and chrysanthemum) extracts and tea components (epigallocatechin gallate and gallic acid) on the attachment of five oral pathogens (Streptococcus mutans ATCC 25175, Streptococcus mutans ATCC 35668, Streptococcus mitis ATCC 49456, Streptococcus salivarius ATCC 13419 and Actinomyces naeslundii ATCC 51655) to the HGF-1 gingival cell line. Extracts of two of the teas (pu-erh and chrysanthemum) significantly (p < 0.05) reduced attachment of all the Streptococcus strains by up to 4 log CFU/well but effects of other teas and components were small. Conclusions: Pu-erh and chrysanthemum tea may have the potential to reduce attachment of oral pathogens to gingival tissue and improve the health of oral soft tissues.